Mitochondrial Dysfunction in Traumatic Brain Injury: Management Strategies - Bonilla-Mendoza, Carlos-Andrés; Garcia-Ballestas, Ezequiel; Pacheco-Hernandez, Alfonso; Moscote-Salazar, Luis-Rafael; Keni, Ravish R.; Agrawal, Amit (Indian Journal of Neurotrauma, 2020)
Today, traumatic brain injuries continue to be studied, increasingly investigating the pathophysiological mechanisms that contribute to the clinical presentation, severity, and possible sequelae, but despite this, the prognosis of these patients is sometimes poor. Mitochondrial dysfunction comprises a series of reactions that contribute to the inflammatory process in these patients that have an impact on the prognosis, since it is one of the pathophysiological mechanisms involved in secondary lesions after a traumatic brain injury; and therefore has opened a field of study in the search of possible biomolecular markers that allow us to establish a prognosis and prediction of mortality.
Keywords: mitochondria; traumatic brain injury; apoptosis